A method to assess lighting quality in educational rooms using analytic hierarchy process. (15th January 2020) - Leccese, F.; Salvadori, G.; Rocca, M.; Buratti, C.; Belloni, E.
Abstract: Nowadays, the belief that lighting can influence comfort, productivity and people's health is well established. In educational rooms the absence of adequate levels of indoor comfort can greatly influence the learning ability of students. The evaluation of lighting indoor quality is often limited to test and check the illuminance levels of the main tasks. However, the lighting quality and the achievement of adequate levels of visual comfort strongly depend on other factors that cannot be overlooked in a detailed analysis. The authors propose an original lighting quality assessment method for the evaluation of lighting in educational rooms, aimed at analysing all the main aspects and at defining a ranking of the critical issues, in order to consider improvements. The method based on the selection of lighting criteria, sub-criteria, and related indicators. Since an analytic hierarchy process was applied to assign a weight to each criterion that has a different impact on the lighting quality. The proposed method was applied at the scale of the single classroom and of a group consisting of six classrooms, considering the buildings of the School of Engineering at University of Pisa as case study. Finally, with the aim of verifying the correspondence between results of the proposed method and actual users' perception, a subjective survey was carried out in the same investigated classrooms. A total of 420 questionnaires were filled, and the results revealed the correspondence between the proposed method and the subjective surveys, proving the validity of the method. Highlights: An original method to assess lighting quality in educational buildings is proposed and discussed. The method is tested on a sample of 6 classrooms representative of an entire university building. The results obtained by the proposed method are compared with those obtained by a subjective analysis. For the subjective analysis, 420 evaluation questionnaires have been administrated to different groups of students. The method has practical-applicative repercussions, guiding improvement interventions of lighting in buildings.